Role of Kurdish Journalism in Strengthening Referendum Process - Hawkar Yaseen Shareef; Magedad Khther Ahmad Sapan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This research focuses on referendum process for independency on 25-09-2017 in the Kurdistan, where most of the people within Kurds, Arabs, Turkmen, and Syrians voted. It was such a unique incident where the region voted to announce its independency from the central government where there are many countries have not witnessed it. This research focuses on an issue where the researcher attempts to demonstrates through this research, which is the Kurdish journalism and Khabat newspaper which is issued in Kurdish language and was capable of shed light on this incident especially during the voting campaign. The objective of this research is the level of successfulness of Khabat newspaper during the voting campaign and the impact of the newspaper’s activities as articles, reports, and interviews during that period. For this, the researcher has used descriptive method through forming questionnaire and distributing amongst readers of Khabat newspaper. The questionnaire consists of two main parts, general information part as gender, age, place, profession, and education level, and the second part is concerning Khabat newspaper during the referendum period, and 508 forms were distributed and the research sample were: (Journalist, employees, people with free job, university professors and students) in Erbil province as the research was conducted in Erbil and Khabat newspaper is in Erbil as well. The result of the research showed that Khabat newspaper was successful in demonstrating the process and the yes and no were cleared to the president of the Kurdistan region and people.